Augmented renal clearance: a retrospective, cohort study of urinary creatinine clearance in critically ill patients in the United Kingdom. Issue 5 (May 2021) - Johnston, Brian W; Perry, David; Habgood, Martyn; Joshi, Miland; Krige, Anton
Objective: Augmented renal clearance (ARC) is associated with sub-therapeutic antibiotic, anti-epileptic, and anticoagulant serum concentrations leading to adverse patient outcomes. We aimed to describe the prevalence and associated risk factors for ARC development in a large, single-centre cohort in the United Kingdom. Methods: We conducted a retrospective observational study of critically unwell patients admitted to intensive care between 2014 and 2016. Urinary creatinine clearance was used to determine the ARC prevalence during the first 7 days of admission. Repeated measures logistic regression was used to determine risk factors for ARC development. Results: The ARC prevalence was 47.0% (95% confidence interval [95%CI]: 44.3%–49.7%). Age, sex, Acute Physiology and Chronic Health Evaluation (APACHE) II score, and sepsis diagnosis were significantly associated with ARC. ARC was more prevalent in younger vs. older (odds ratio [OR] 0.95 [95%CI: 0.94–0.96]), male vs. female (OR 0.32 [95%CI: 0.26–0.40]) patients with lower vs. higher APACHE II scores (OR 0.94 [95%CI: 0.92–0.96]). Conclusions: This patient group probably remains unknown to many clinicians because measuring urinary creatinine clearance is not usually indicated in this group. Clinicians should be aware of the ARC risk in this group and consider measurement of urinary creatinine clearance.